Experiencing Progressive Rock by Robert G. H. Burns. (4th October 2019) - Vallen, Sam
Abstract : Robert G. H. Burns, Experiencing Progressive Rock. Lanham, MD: Rowman & Littlefield, 2018. 261 pp. ISBN 978-1-44226-602-5 (hbk).